Fainting Starting Parenteral Nutrition. - Pederiva, Federica; Barbi, Egidio; Zennaro, Floriana; Neri, Elena (Pediatr Emerg Care, 2015)
Complications such as mechanical accidents, infections, and thrombosis are commonly described in the presence of a central venous catheter. We present a case of a boy who had fainting episodes due to dislocation of a central venous catheter.